Optimizing Cycling Conditions for Anode-Free Lithium Metal Cells. Issue 2 (5th February 2021) - Louli, A. J.; Coon, Matt; Genovese, M.; deGooyer, Jack; Eldesoky, A.; Dahn, J. R.
Abstract : Optimizing the performance of the lithium metal anode is required to enable the next generation of high energy density batteries. Anode-free lithium metal cells are particularly attractive as they facilitate the highest energy density cell architecture. In this work, we investigate the performance of anode-free cells cycled under different protocols. We demonstrate the impact of charge and discharge current density with three different cycling conditions: a symmetric charge-discharge, an asymmetric faster charge and an asymmetric slower charge. We show that the relative rate of charge vs discharge is more important than the absolute current densities, and that cycling with an asymmetric slower charge protocol is optimal in agreement with previous studies on cells with lithium metal anodes. We also examine the effect of depth of discharge and demonstrate how the lower voltage cut-off can be chosen to form a lithium reservoir in situ. We show that the capacity of the lithium reservoir significantly benefits lifetime for cells cycled with a limited depth of discharge. Finally, we develop a specialized intermittent high depth of discharge cycling protocol optimized for anode-free lithium metal cells.